Arboreal Being: Encounters with Trees in Recent Southern African Fiction - Woodward, Wendy (Journal of Literary Studies, 2019)
Because trees tend to be objectified, labelled botanically without any awareness of the import of their presence, the novels and short story considered in this article are unusual. Zakes Mda’s The Heart of Redness (2000), Niq Mhlongo’s Soweto, Under the Apricot Tree (2018), Mia Couto’s Under the Frangipani (2001) and Beverley Rycroft’s A Slim Green Silence (2015) foreground the presence of trees in their narratives, all implicitly critiquing a “culture” which neglects to acknowledge a tree in its full significance. In The Heart of Redness, Zim merges with ancestral time via his beloved fig tree. The title short story in Soweto, Under the Apricot Tree depicts the eponymous tree as both a material participant in apartheid history as well as a link to indigenous beliefs. In Under the Frangipani, Mucanga, the main character, attains his desired oblivion from the narrative self as he merges with “plant life”. Yellowwoods feature centrally in the awareness of Connie’s spirit in A Slim Green Silence. Merging into arboreal being has ontological implications for the characters as well as a broader animist significance. At the same time, the trees are biopolitical subjects rooted in the temporal environment. Opsomming Aangesien bome, sonder die minste aandag aan die belang daarvan, summier geobjektiveer en botanies benoem word, is die romans en kortverhaal waaroor hierdie artikel handel, in vele opsigte merkwaardig. In Zakes Mda se roman The Heart of Redness (2000), Niq Mhlongo se kortverhaalbundel Soweto, Under the Apricot Tree (2018), Mia Couto se roman Under the Frangipani (2001) en Beverley Rycroft se A Slim Green Silence (2015) tree bome op die voorgrond as implisiete kritiek teen 'n “kultuur” waarin die belang van bome onderskat word. In The Heart of Redness reis Zim deur sy dierbare vyeboom terug na die tyd waarin sy voorouers geleef het. Die gelyknamige boom in die titelkortverhaal in Soweto, Under the Apricot Tree tree gelyktydig as 'n wesenlike deelnemer aan die apartheidsgeskiedenis en 'n band met inheemse opvattings op. In Under the Frangipani ontkom die hoofkarakter Mucanga aan die narratiewe self wanneer hy in die “plantlewe” opgeneem word. Geelhoutbome speel in die roman A Slim Green Silence ’n wesenlike rol in die bewussyn van Connie se gees. Eenwording met 'n arboriese wese hou ontologiese implikasies vir die karakters in, en het ook nog 'n breë animistiese strekking. Bome is terselfdertyd biopolitiese subjekte wat in 'n aardse omgewing gewortel is.